The Role of Product Placement, Celebrity Endorser, & Product Innovation in Brand Awareness Wall’s Popcornetto - Clarinta, Laisya Kezia; Prabowo, Budi (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study analyzes the role of product placement, celebrity endorsers, and product innovation in enhancing the brand awareness of Wall’s PopCornetto. Marketing strategies play a crucial role in enhancing brand awareness, particularly in the highly competitive ice cream industry. As one of Unilever Indonesia's innovative products, Wall’s PopCornetto applies these strategies to strengthen its brand presence among consumers. The rapid expansion of digital media, especially YouTube and Instagram, presents new opportunities for brands to increase visibility and consumer engagement through creative marketing approaches. This research uses a quantitative associative approach with purposive sampling of 100 respondents. The respondents are Instagram followers of Wall’s Cornetto, have watched Wall’s PopCornetto advertisements on the Iqbaal program on the VINDES YouTube channel, recognize Refal Hady as a celebrity endorser, and know Wall’s PopCornetto product. Data collection was carried out through a questionnaire using a Likert scale, and the analysis was conducted using SPSS 25 with validity and reliability tests, multiple linear regression, and hypothesis testing. The results showed that product placement, celebrity endorser, and product innovation significantly affect brand awareness, both partially and simultaneously. Among these variables, celebrity endorsers had the highest influence on brand awareness, indicating that a well-known and credible public figure can effectively attract consumer attention and reinforce product recall.